PENGUATAN MUTU JASA MELALUI PELATIHAN LITERASI INFORMASI PERPUSTAKAAN DALAM MENDUKUNG SUSTAINABLE DEVELOPMENT GOALS - Aprilia, Fachrina; Ishmah, Nur; Azizah, Laila Rifa?atul (Journal of Documentation and Information Science, 2019)
Educational institutions included in service providers the category. The services? usually includes scholarships, assessments, providing guidance to the students, parents, and sponsors. As the heart of the university, library has an important role in strengthening the academic quality of students. In addition to providing quality resources for students, many libraries had implemented training programs for information literacy for university academic community. The literacy training program intended for the academic community to literate with the information , seeking the valid information and use the information based on the needs. The need for valid information makes education as agent of change and sustainable development naturally be a key part that integrates the 17 points of SDG's? which is the goal of sustainable development. Therefore, information literacy program implemented by the library is one effort in supporting the realization of SDG's in education. UMM library has run several functions such as education, research, and the information set forth in a form of information literacy training with the aim to educate, guide students in doing research, and information sharing. UMM library has also implemented a literacy program which is considered very important for the academic community. That is because the density of the material provided in this training is expected to increase the competence of the academic community in the face of the information era. The information literacy training has been followed by many students and lectures at the University of Muhammadiyah Malang. Students who attend this training average wending towards the thesis and thesis writing. While the lecturers usually groups and individuals participated in this information literacy training. A lot of knowledge and skills acquired by the participants of this information literacy training. And along the communication with the participants, the participants were very enthusiastic and happy to gain experience and new abilities through this literacy training.